THE FUNCTIONS AND IMPORTANCE OF REPRESENTATION OF STATES IN THEIR RELATIONS WITH INTERNATIONAL ORGANIZATIONS OF A UNIVERSAL CHARACTER - Gregorius Sri Nurhartanto (Faculty of Law Universitas Lampung, 2022)
The development of International relations have rapidly since the signing of Westphalia Treaty in 1648. The relationship are not only between States but also by public international organizations (Inter Governmental Organizations). After the Second World War, the establishment of the United Nations and its Specialized Agencies and Other Organs has encouraged the intensive of international cooperation and the making of treaties as a source of international law. The United Nations and its Special Agencies and Other Organs is often called as an international organization of a universal character. Both States members and non-States members establish cooperation with this universal international organization. The existence of State representation in a universal international organization with a universal character is very important for strengthening the cooperation between States and international organizations.